The Brahmans’ Utopia from the Greek Sources to John of Salisbury’s Policraticus - Di Serio, Chiara (In Gremium. Studies in History, Culture and Politics, 2021)
This work focuses on the Graeco-Roman sources which describe the remote space inhabited by the Brahmans, the Indian sages who met Alexander the Great. The aim of the research is to illustrate: a) the impact of the descriptions by Greek authors who employ the topos of the spatial remoteness of the Brahmans from the Western world; b) how the same theme becomes even more evident in the late antique sources up to the medieval texts, among which a passage from John of Salisbury’s Policraticus constitutes a relevant part of the investigation.